Development of managerial competencies of future teachers in universities of Kazakhstan and Lithuania (Journal of Educational Sciences, 2023)
The article discusses the content of the concept of «managerial competence of future teachers». The authors substantiated the relevance and importace of developing managerial competencies in future teachers. Particular attention is paid to working with theoretical sources of information. In the same way, a detailed analysis of the training of future teacher-managers in the leading universities of Kazakhstan and Lithuania is presented. The study of the content of educational programs on management in education in Lithuania made it possible for the authors to identify the most valuable ideas of foreign experience. The article describes a set of means, methods of comparative pedagogy, which allowed the authors to conduct a study in accordance with the goal. Based on the theoretical studies, the features of the development of management programs in education were identified. The authors point out specific differences in the structure of the programs, and in the presentation of educational material. At the same time, based on a comparative characteristic, attention is focused on the fact that in the content of the educational program on management in education in our country, there is a certain similarity with the Lithuanian program. This similarity is manifested in the general approaches to the selection of content. Also, the authors of this article had the opportunity to conduct a method of comparison and synthesis, to consider the features of the formation of the managerial competence of future teachers and to study the key aspects of the development of managerial competence of teachers in the context of transformational processes in the education of the Republic of Kazakhstan. Key words: management, managerial activity, managerial competence, future teachers.